Perancangan Alat Uji Putaran Kritis Poros Menggunakan Digital Counter - Hihamsyah, Diva Puperta; Mukhnizar, Mukhnizar; Abu , Risal; Afdal, Afdal; Selviyanty, Veny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Shaft critical rotation test tool to calculate the maximum deflection on the shaft, the size of the force or pressure is directly proportional to the amount of deflection. Currently the critical shaft rotation test tool is still manual. From the problems above, the author designed a critical shaft rotation test tool using a digital counter (sensor) to read the rotation precisely and accurately, motor power ¼ HP 2800 Rpm rotation. The critical rotation test tool for the shaft has the working principle of using an electric motor where this motor transmits power from the drill chuck to the shaft. The process of planning the critical rotation test tool consists of: power Pd = 0.3 kw, shaft material S30C with ?20 length 1500 mm, bearing type 6204 , bolts ? 12 mm, bolts ? 14, The load used is iron with dimensions ?l 150 mm, ?d 20 mm and a thickness of 10 mm, Drill chuck used as a supporting specimen with a supporting diameter of 20 mm, Frame size 1800 mm x 750 mm x 750mm